Corporate structural change for tax avoidance: British multinational enterprises and international double taxation between the First and Second World Wars. Issue 4 (19th May 2022) - Izawa, Ryo
ABSTRACT: This study demonstrates the actual impact of international double taxation on the management of British multinational enterprises between the First and Second World Wars. In particular, it focused on tracing the process by which the tax-minimisation strategy affected corporate-level strategy. In three cases examined using corporate archival sources, the companies reorganised their corporate legal structure for tax avoidance. Yet the effects on their management were not uniform. (1). The corporate structural change for tax avoidance of Rio Tinto and Silica Gel Corporation did not alter the extant corporate strategy. (2). Tax strategy of Imperial Continental Gas Association entailed changing extant corporate strategy. (3). The legal structure of Unilever gradually and unintentionally influenced the extant corporate strategy. These heterogeneous responses of the firms imply that the institutional pressure of a tax law does not always lead to organisational isomorphism and can affect the corporate-level strategy over time.